موقف النحويين العرب من التعليل النحوي حتى القرن السادس الهجري - عوض, سامي; عبود, يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
النحو هو روح اللغة وجوهر حركتها وقلبها النابض ، وطريقُ التعليل فيه طريقٌ ذهني خالص، سَلَكه النحويون العرب، وقدّموا فيه جهداً كبيراً في سبيل تفسير قواعدهم النحوية والصرفية . يتّخذ البحثُ الآتي من آراء بعض النحويين القدامى والمعاصرين منطلقاً لدراسة التعليل النحوي على مستويين: المستوى الأول هو مستوى المفهوم والمنهج ؛ حيث يَرْصد مفهومَ التعليل في النحو، وانعكاسات هذا المصطلح على قواعده، وبيان موجباته التي يتأسس عليها في الاستخدام اللغوي. والمستوى الثاني هو مستوى المرجعية؛ إذْ يستحضرُ البحثُ من خلاله آراءَ النحويين في العلّة ومواقفهم من التعليل النحوي حتى القرن السادس الهجري. The syntax is the spirit of language , the core of its movement, it is living heart. And it is way of interpretation which is a pure mental manner . Taken by Arab Grammarians, so they gave it great effort in order to interpret the syntactic and morphological bases . The following research considers the most important views of the old and modern syntax-specialists as starting point of studying the syntax – interpretations at two levels : the first Level contains concept and approach, It monitors the concept of reasoning in as, and the implications at rules of this term, the statement its motive which is based language in use . and the second level is referential . It demands its elements and the views of Arab syntax in it , and it clears its rules which was established tell the six migration century .